Configuration of Canal System in the Mesiobuccal Root of Maxillary First Molars - Spalding, Marianne; Rezende, Karla Mayra; Garcia Silveira, Maria Claudia; Valera, Marcia Carneiro; Leite, Horacio Faig (Soc Chilena Anatomia, 2017)
Knowledge on internal dental morphology is extremely important to the correct execution of the treatment and modeling of root canals. The aim of the present study was to analyze, in vitro, the configuration of the canal system in the mesial root of 180 maxillary first molars obtained from a Brazilian sample. The teeth diaphanized in order to confirm the presence of the MB2 canal and to determine the internal anatomy. Only in 41 % of the teeth the orifice of MB2 canal emerged from the pulp chamber floor. Among teeth two apical foramina were found in 23.3 %, a single apical foramen was observed in 15,5 % and three apical foramina were present in 2,2 %. Considering the hole sample, the MB2 canal was observed in 65.4 %, merged with the MB1 or branching from the MB1 or even independent all the way. In 55.1 % of the teeth a single orifice stemmed from the pulp chamber floor. A single apical foramen was found in 43,5 % of these cases, two apical foramina were present in approximately 12 % and apical delta was found in 0,5 % of the specimens. Three orifices which emerged from the pulpal floor were observed in 1.1 % of the sample. Paths considered very atypical were observed at 2.8 % of the teeth. The MB root canal anatomy was complex. The frequency of occurrence of the bifurcated or double canal, isthmus, accessory canals and apical delta must be taken into consideration as a possible cause of otherwise unexplained failure during endodontic treatment of first maxillary molars.
Keywords: Molar; Root canal; Anatomy; Endodontics